The Example of Mersin in the Sustainability of Coastal Cities under the Impact of Climate Change - Nihal Zengin; Ruşen Yamaçlı (Doğal Afetler ve Çevre Dergisi)
It is seen that cities, which have hosted different cultures and civilizations in the historical process and have a lively and dynamic structure, have been shaped with different characteristics under the influence of many factors. Topography, water and railroads, historical and social values are shown as important factors in the shaping of the city. In general, coastal cities established along the coasts of sea and lake shores have received immigration as a result of the opportunities they offer and new places have been produced in order to meet the needs and demands of the increasing population. As a result, the building stock has increased rapidly and the city forms have changed. Coastal cities, where the population, production and consumption are high, are directly affected by global warming and the climate change it brings with it, which has been felt more in recent years. In this research article, it is aimed to increase the current and future performance of Mersin city and its components selected as a field study in adapting and combating global warming and climate change. In this context, the national and international literature has been analyzed in depth and the way cities located on the coasts of the world have followed in adapting and combating climate change has been examined in detail. As a result of the article, in order to use it as a base for creating resistant and sustainable settlements in coastal cities, in particular the city of Mersin, which is located on the coast, what needs to be done in adaptation and combating with climate change is listed.